2003
DOI: 10.1021/ma034643l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hyperbranched Polysaccharide by Thermally Induced Cationic Polymerization of 1,6-Anhydro-β-d-mannopyranose

Abstract: The thermally induced cationic polymerization of 1,6-anhydro-β-d-mannopyranose (1) as a latent cyclic AB4-type monomer was carried out using 2-butenyltetramethylenesulfonium hexafluoroantimonate (2) as the initiator. The solution polymerization in propylene carbonate proceeded without gelation to produce the water-soluble hyperbranched polysaccharides (3) with controlled molecular weights and narrow polydispersities. The weight-average molecular weight (M w,SLS) values of 3 measured by static laser light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…In order to alleviate this problem, we chose the solution polymerization of 1,6-anhydro-b-D-hexopyranose using a thermally induced cationic initiator, as shown in Scheme 1. [43,46,47] Table 1 summarizes the polymerization results of 1,6-anhydro-b-D-glucopyranose (1a), 1,6-anhydro-b-D-mannopyranose (1b), and 1,6-anhydrob-D-galactopyranose (1c) using (S-2-butenyl)tetramethylenesulfonium hexafluoroantimonate (2).…”
Section: Synthesis Of Hyperbranched Polysaccharide By Thermally Inducmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to alleviate this problem, we chose the solution polymerization of 1,6-anhydro-b-D-hexopyranose using a thermally induced cationic initiator, as shown in Scheme 1. [43,46,47] Table 1 summarizes the polymerization results of 1,6-anhydro-b-D-glucopyranose (1a), 1,6-anhydro-b-D-mannopyranose (1b), and 1,6-anhydrob-D-galactopyranose (1c) using (S-2-butenyl)tetramethylenesulfonium hexafluoroantimonate (2).…”
Section: Synthesis Of Hyperbranched Polysaccharide By Thermally Inducmentioning
confidence: 99%
“…In order to confirm the branching and manner of linkage of the repeating units, a methylation analysis of 3a-c was carried out according to a reported method. [43,47,[50][51][52] The identified repeating units were classified into five categories of terminal units (T), linear units (L), two semidendritic units with three and four linkages (sD 1 and sD 2 , respectively), and perfect dendritic units (D) with five linkages, as shown in Figure 1 The results of the methylation analysis showed that the reaction with the C-6 position was apparently favored. For the solution polymerization of 1a, the C-3 hydroxyl groups were less reactive than the C-2 and C-4 hydroxyl groups; that is, the reactivity increased in the order of C-6 ) C-2 ¼ C-4 > C-3, but C-6 ) C-2 > C-4 > C-3 for 1b, and C-6 ) C-3 > C-2 > C-4 for 1c.…”
Section: Synthesis Of Hyperbranched Polysaccharide By Thermally Inducmentioning
confidence: 99%
“…However, hyperbranched polysaccharides (HBPs), including amylopectin, glycogen and some glucans from mushroom cell walls, have attracted increasing attention in the fields of nanotechnology and pharmacology because of their unique structures and properties [141][142][143]. The spherical architecture of highly branched macromolecules provides numerous terminal units that can be converted into various functional groups leading to novel nanomaterials [32,144].…”
Section: Hyperbranched Polysaccharidesmentioning
confidence: 99%
“…Several other anhydrosugars have been polymerized in the following years. 53,54,[93][94][95][96][97][98] Anhydrosugars containing a tetrahydrofuran scaffold are rather expensive monomers. Therefore, the group of Bednarek and Kubisa focused on the polymerization of tetrahydrofurans substituted with hydroxyl groups, mainly 2-(hydroxymethyl)tetrahydrofuran, but also 3-hydroxytetrahydrofuran and 3,4-dihydroxytetrahydrofuran.…”
Section: Figure 11mentioning
confidence: 99%